2023
DOI: 10.1656/058.022.0sp1206
|View full text |Cite
|
Sign up to set email alerts
|

New Location Records for Alligator Snapping Turtle (Macrochelys temminckii) Captured during Fishery Surveys in Alabama

Steven J. Rider,
Travis R. Powell,
Gregory T. Miles

Abstract: Macrochelys temminckii (Alligator Snapping Turtle) is classified as a species of moderate conservation concern by the State of Alabama and is proposed for listing as threatened under the Endangered Species Act by the US Fish and Wildlife Service. Using the most up-to-date and best available distribution and biological data is paramount in the decisionmaking process for any petitioned or proposed-listed species. We provide an additional 21 Alligator Snapping Turtle records from Alabama collected as bycatch duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…If these were native Alabama Shad, then it would be the only known occurrences of the species above the fall line in any Mobile Basin tributary from that time. Much later, between 1950 and 1964, Royal Suttkus collected hundreds of adult and juvenile Alabama Shad above and below the fall line in the Cahaba River (Rider et al., 2021). Interestingly, the Cahaba River was the only tributary without a dam.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If these were native Alabama Shad, then it would be the only known occurrences of the species above the fall line in any Mobile Basin tributary from that time. Much later, between 1950 and 1964, Royal Suttkus collected hundreds of adult and juvenile Alabama Shad above and below the fall line in the Cahaba River (Rider et al., 2021). Interestingly, the Cahaba River was the only tributary without a dam.…”
Section: Resultsmentioning
confidence: 99%
“…Alabama Shad would have had to be snagged or trapped to be captured, which was very rarely reported, especially in the coastal plain where traps were less common. Furthermore, it has been found that Alabama Shad prefer sand‐bottom rivers with limestone outcrops for spawning, which are much more common below the fall line (Rider et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gill nets are a type of entanglement device used primarily in commercial fisheries and fisheries research (Hubert et al 2013). Barko et al (2004) and Rider et al (2023 [this issue]) reported low rates of turtle bycatch using gill nets. Barko et al (2004) did not work within the geographic range of M. temminckii but did capture Common Snapping Turtles using the 5 gear types compared; gill nets had the lowest turtle bycatch rate.…”
Section: Discussionmentioning
confidence: 99%
“…Barko et al (2004) did not work within the geographic range of M. temminckii but did capture Common Snapping Turtles using the 5 gear types compared; gill nets had the lowest turtle bycatch rate. Rider et al (2023 [this issue]) reported capturing M. temminckii in Alabama at a rate of ∼0.079 per gill net-night (24-h period). We recorded 1 instance of a Louisiana commercial fisherman capturing a 40-kg M. temminckii in a gill net (see ).…”
Section: Discussionmentioning
confidence: 99%